EFFECT OF CORPORATE RESTRUCTURING ON EMPLOYEE MORALE: EVIDENCE FROM AIRTEL NIGERIA LIMITED - Obi, James Nwoye; Sajuyigbe, Ademola Samuel; Peter, Fred Ojochide (APPS Publications, 2021)
Corporate restructuring is the act of re-organizing the operations of a firm in order to eliminate waste, promote efficiency, increase profitability, and ensure organizational sustainability. Yet there has been a dearth of empirical studies on the effect of corporate restructuring on employee morale. The study sought to examine the extent to which work process has effect on employee punctuality, the extent to which organizational structure affects employee turnover rate and how an altered physical environment influences interpersonal relationships among employees. Data were sourced from three hundred and eighty (380) participants. The results of the regression analyses showed that change in the work process has a significant effect on employee punctuality at work, change in organizational structure has a significant effect on employee turnover rate and altered physical environment influences inter-personal relationships among workers. It was recommended that corporate organizations embarking on restructuring should take into consideration the effect of the exercise on employee morale in the interest of superior performance.